Parent perspectives on oncology team communication regarding neurocognitive impacts of cancer therapy and school reentry. Issue 1 (29th August 2018) - Ruble, Kathy; Paré‐Blagoev, Juliana; Cooper, Stacy; Martin, Allison; Jacobson, Lisa A.
Abstract: Background: Neurocognitive deficits are common after childhood cancer and impact academic performance. Parents need to be knowledgeable of long‐term complications impacting school and the resources necessary to support educational achievement. The oncology team plays an important role in preparing parents for the challenges of returning to school after treatment. Methods: An online survey developed by parents and stakeholders was used to assess parent experiences and preferences associated with oncology team support around neurocognitive deficits and school transition. Recruitment included social media sites, foundation contacts, and clinic/event flyers. Topics included information content, timing, and frequency of information; and utility or perceived value of information. Inclusion criteria included respondent identifying as a parent (caregiver) of child treated for cancer who has returned to school. Results: Surveys from 203 parents were completed representing diverse geographic locations. Nearly half (48%) did not recall receiving information about neurocognitive deficits. The most frequently reported time to receive this information was at diagnosis, but parents reported a need for conversations throughout the cancer trajectory, especially at transition to survivorship and school reentry. In addition, half of the parents (51%) felt inadequately prepared for the return to school. Information about neuropsychological testing, resources for learning difficulties, educational terms, and legal rights related to school services were the topics most inadequately provided. Conclusions: Parents feel inadequately prepared by their oncology team for their child's return to school. Research is needed to identify effective oncology team approaches to fill the gaps in knowledge around school reentry after cancer treatment.